Effects of institutional history and leniency on collusive corruption and tax evasion - Johannes Buckenmaier; Eugen Dimant; Luigi Mittone (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2018)
We investigate the effects of an institutional mechanism that incentivizes taxpayers to blow the whistle on collusive corruption and tax compliance. We explore this through a formal leniency program. In our experiment, we nest collusive corruption within a tax evasion framework. We not only study the effect of the presence of such a mechanism on behavior, but also the dynamic effect caused by the introduction and the removal of leniency. We find that in the presence of a leniency mechanism, subjects collude and accept bribes less often while paying more taxes, but there is no increase in bribe offers. Our results show that the introduction of the opportunity to blow the whistle decreases the collusion and bribe acceptance rate, and increases the collected tax yield. It also does not encourage bribe offers. In contrast, the removal of the institutional mechanism does not induce negative effects, suggesting a positive spillover effect of leniency that persists even after the mechanism has been removed.
Keywords: C92; D02; D73; H26; K42; 330; Collusive bribery; Institutions; Tax compliance; Leniency; Spillover